The impact of psychological violence in the workplace on turnover intention of clinical nurses: the mediating role of job satisfaction - Yanyan Luo; Minli Zhang; Shuliang Yu; Xiubi Guan; Ting Zhong; Qingcai Wu; Yuanfang Li (BMC Nursing)
Abstract Background The global nursing shortage, driven by high turnover rates, significantly impacts healthcare quality. Workplace psychological violence severely affects nurses' mental health and job satisfaction, leading to increased turnover. Despite extensive research on workplace violence, the specific impact of psychological violence on nurses' turnover intentions remains insufficiently explored. This study investigates the mediating role of job satisfaction in the relationship between workplace psychological violence and nurses' turnover intentions. Methods A workplace psychological violence scale, a job satisfaction scale, and a turnover intention questionnaire were utilized to survey 206 clinical nurses in a tertiary-level hospital in Guangzhou City. The study employed a convenience sampling method. Statistical analyses included correlation, mediation analyses., descriptive statistics, multivariate linear hierarchical regression analyses, Pearson correlation analyses, and structural equation models. Results Clinical nurses reported a workplace psychological violence score of 0.97 ± 0.79, job satisfaction of 3.16 ± 0.58, and turnover intention of 2.22 ± 0.92. Workplace psychological violence was negatively correlated with job satisfaction (r = -0.516, P < 0.01) and positively correlated with turnover intention (r = 0.418, P < 0.01). Turnover intention was negatively correlated with job satisfaction (r = -0.477, P < 0.01). Mediation analysis indicated that Job satisfaction partially mediated the association between workplace psychological violence and turnover intention. The total effect (β = 0.489) of workplace psychological violence on turnover intention included its direct effect (β = 0.274) and the indirect effect mediated through job satisfaction (β = 0.215), with the mediating effect accounting for 43.97% of the total effect. Conclusions Workplace psychological violence directly predicts nurses' turnover intention, with job satisfaction serving as a mediator in this relationship. Healthcare managers can mitigate psychological violence by improving mental health support, work environments, and organizational culture to enhance job satisfaction and reduce nurse turnover.